ICTs and agricultural entrepreneurship - Lohento, Ken; Speer, Mark (Technical Centre for Agricultural and Rural Cooperation, 2014)
A workshop on youth, ICTs, entrepreneurship and agriculture discussed young people's experiences developing applications and software for the agricultural sector.